# Find the value of the following expressions, when x = -1:

(i) 2x - 7 (ii) - x + 2 (iii) x^{2 }+ 2x + 1 (iv) 2x^{2} - x - 2

**Solution:**

(i) 2x – 7

Since, it is given that x = -1

By substituting the value of x in the given expression, we get

= 2 × (-1) - 7

= - 2 - 7

= - 9

(ii) - x + 2

Since, it is given that x = -1

By substituting the value of x in the given expression, we get

= - (-1) + 2

= 1 + 2

= 3

(iii) x^{2} + 2x + 1

Since, it is given that x = -1

By substituting the value of x in the given expression, we get

= (-1)^{2} + 2 × (-1) + 1

= 1 - 2 + 1

= 2 - 2

= 0

(iv) 2x^{2} – x – 2

Since, it is given that x = -1

By substituting the value of x in the given expression, we get

= 2 × (-1)^{2} - (-1) - 2

= (2 × 1) + 1 – 2

= 2 + 1 – 2

= 3 – 2

= 1

**☛ Check: **NCERT Solutions for Class 7 Maths Chapter 12

**Video Solution:**

## Find the value of the following expressions, when x = –1: (i) 2x – 7 (ii) – x + 2 (iii) x² + 2x +1 (iv) 2x² – x – 2

Maths NCERT Solutions Class 7 Chapter 12 Exercise 12.3 Question 3

**Summary:**

The value of the following expressions, when x = –1: (i) 2x – 7 = - 9 (ii) – x + 2 = 3 (iii) x^{2} + 2x + 1 = 0 (iv) 2x^{2} – x – 2 = 1

**☛ Related Questions:**

- If A 2 B 2 Find The Value Of I A2 B2 Ii A2 Ab B2 Iii A2 B2
- When A 0 B 1 Find The Value Of The Given Expressions I 2a 2b Ii 2a2 B2 1 Iii 2a2b 2ab2 Ab Iv A2 Ab 2
- Simplify The Expressions And Find The Value If X Is Equal To 2 I X 7 4 X 5 Ii 3 X 2 5x 7 Iii 6x 5 X 2 Iv 42x 1 3x 11
- Simplify These Expressions And Find Their Values If X 3 A 1 B 2 I 3x 5 X 9 Ii 2 8x 4x 4 Iii 3a 5 8a 1 Iv 10 3b 4 5b V 2a 2b 4 5 A

visual curriculum